Statins Do Not Influence Long-Term Rituximab Clinical Efficiency in Rheumatoid Arthritis Patients. (8th January 2014) - Mazilu, Diana; Gudu, Tania; Ionescu, Ruxandra; Opris, Daniela
Abstract : Objective . This longitudinal study aims to determine if statins inhibit the response to rituximab in rheumatoid arthritis (RA) patients. Methods . 41 patients initiating rituximab were included; 17 patients were exposed to the combination of statins and rituximab. The total cholesterol, erythrocyte sedimentation rate (ESR), and C-reactive protein (CRP) were assessed. The clinical response was evaluated using Disease Activity Score (DAS28) and European League against Rheumatism (EULAR) response at 6 and 18 months. Results . A tendency of increasing in DAS28 was observed in statin-exposed group but the correlation was very weak (at 18 months: r = 0.013, P = 0.952 ). The statin-exposed status was negatively and very weakly correlated with EULAR response at 6 months (r = - 0.073, P = 0.661 ) and 18 months (r = - 0.197, P = 0.244 ). There was a negative correlation between statin-exposed status and inflammatory markers values (ESR and CRP); however, the correlation was very weak. The use of statin did not influence the cardiovascular risk measured by modified Systematic Coronary Risk Evaluation (mSCORE). Conclusions . Long-term significant inhibitory effects of statins on rituximab treatment in RA have not been proved using clinical response scores or biologic markers.